Pengaruh Kinerja Guru dalam Pelaksanaan Pembelajaran terhadap Prestasi Belajar Siswa pada Mata Pelajaran Alquran Hadis - Sodik, Mohamad; Sahal, Yosef Farhan Dafik; Herlina, N. Hani (Jurnal Penelitian Pendidikan Islam, 2019)
This research is motivated by the discovery of problems related to the performance of teachers in the implementation of learning the Qur'an-Hadith. After conducting an interview with the school principal, it turns out that students experience and feel how a teacher is carrying out learning, Class V in MIN 10 Ciamis student grades are above the KKM as a whole with an average of 84.59. Therefore research is needed regarding the effect of teacher performance in the implementation of learning. The purpose of this study is: to determine the performance of teachers in the implementation of learning the subjects of Qur'an-Hadith class V at MIN 10 Ciamis, to determine student learning achievements in subjects Qur'an-Hadith class V at MIN 10 Camis, to find out the effect of teacher performance in the implementation of learning on student achievement in the subjects of the Koran class V in Hadith 10 Ciamis. To get the data of this study, the authors used a descriptive correlational method with a quantitative approach and used data collection techniques with observation, distributing questionnaires to 39 respondents, interviews and documentation studies. The results of this study indicate that the Significance value of 0.959> 0.05, which means that there is an influence of teacher performance in the implementation of learning on student achievement in the subjects of Qur'an-Hadith class V at MIN 10 Ciamis